PEMODELAN STABILITAS BENDUNG MAROS DENGAN MENGGUNAKAN APLIKASI SAP2000 - Riswal Karamma; Ahmad Syarif Sukri (semanTIK, 2019)
Analysis of the stability of the weirs can be compared with the results of the modeling application using SAP2000 stability that can reveal a condition safe and critical of the results of the design of weirs. The results of modeling the structure of maximum voltage-generating dam hold 30.354186 t/m2 occurred in the bottom of the pond while the maximum voltage refuses 16.811126 t/m2 occurred in the top of the outdoor refuse. A load of mud shows a voltage of-4.194299 t/m2 and 2.626117 t/m2, load the normal voltage-generating water 47.18661 t/m2 and 31.412491 t/m2 load voltage-generating flood water 24.214049 t/m2 and 11.098479 t/m2. The results suggested the presence of part of the structure that is experiencing a critical condition. Part of the structure that has the maximum voltage value is the weakest part of the construction area.Keywords—Stabilility,Weir, SAP2000 DOI : 10.5281/zenodo.2652067